Current possibilities and future opportunities provided by three-dimensional lung ECM-derived hydrogels - Nizamoglu, Mehmet; Burgess, Janette K. (Frontiers in Pharmacology, 2023)
Disruption of the complex interplay between cells and extracellular matrix (ECM), the scaffold that provides support, biochemical and biomechanical cues, is emerging as a key element underlying lung diseases. We readily acknowledge that the lung is a flexible, relatively soft tissue that is three dimensional (3D) in structure, hence a need exists to develop in vitro model systems that reflect these properties. Lung-derived ECM hydrogels have recently emerged as a model system that mimics native lung physiology; they contain most of the plethora of biochemical components in native lung, as well as reflecting the biomechanics of native tissue. Research investigating the contribution of cell:ECM microenvironment to acute and chronic lung diseases has begun adopting these models but has yet to harness their full potential. This perspective article provides insight about the latest advances in the development, modification, characterization and utilization of lung-derived ECM hydrogels. We highlight some opportunities for expanding research incorporating lung-derived ECM hydrogels and potential improvements for the current approaches. Expanding the capabilities of investigations using lung-derived ECM hydrogels is positioned at a cross roads of disciplines, the path to new and innovative strategies for unravelling disease underlying mechanisms will benefit greatly from interdisciplinary approaches. While challenges need to be addressed before the maximum potential can be unlocked, with the rapid pace at which this field is evolving, we are close to a future where faster, more efficient and safer drug development targeting the disrupted 3D microenvironment is possible using lung-derived ECM hydrogels.